1983
DOI: 10.1161/01.str.14.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of relaxant action of nicardipine, a new Ca++-antagonist, on isolated dog cerebral and mesenteric arteries.

Abstract: SUMMARY In helically-cut strips of cerebral and mesenteric arteries contracted with prostaglandin (PG) F^, carbocyclic thromboxane A 2 (cTxA 2 ) or K + , the addition of nicardipine caused a dose-related relaxation. Nicardipine-induced relaxation was greater in cerebral than in mesenteric arteries when contracted with PGF 2a and cTxA 2 , but did not appreciably differ in the arteries contracted with K + . Cerebral arteries contracted with hemolysate and PGF 2a relaxed in response to nicardipine to a similar ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Therefore, the rate of VS found in this study may be considered extremely low. The mean concentration of nicardipine in the CSF 12 h after the intrathecal administration was 231.44 ng/ml, which matches the effective concentration revealed by in vitro study at 10 -9 -10 -5 M (molecular weight of nicardipine is 515.99) [36]. In this study, nicardipine was administered every 12 h, so the effective concentration was likely maintained during the interval between each administration, and the fewer incidences of VS in this study may be partly due to the nicardipine in the CSF.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the rate of VS found in this study may be considered extremely low. The mean concentration of nicardipine in the CSF 12 h after the intrathecal administration was 231.44 ng/ml, which matches the effective concentration revealed by in vitro study at 10 -9 -10 -5 M (molecular weight of nicardipine is 515.99) [36]. In this study, nicardipine was administered every 12 h, so the effective concentration was likely maintained during the interval between each administration, and the fewer incidences of VS in this study may be partly due to the nicardipine in the CSF.…”
Section: Discussionsupporting
confidence: 81%
“…43 " 45 NC and its dihydropyridine relatives block calcium uptake by membrane fractions from cerebral arteries 46 resulting in relaxation of smooth muscle in the walls of cerebral arteries and arterioles. 47 " 49 Dihydropyridine binding sites are also present in cerebral tissue 50 - 51 and a dihydropyridine-sensitive calcium channel has been identified in neuronal soma, 51 suggesting that these drugs might be effective in modifying calcium entry into neurons. In previous studies we have demonstrated substantial extraction of unchanged NC into normal and ischemic rat brain 21 and have demonstrated improved neuronal function after subcutaneous infusion.…”
Section: Discussionmentioning
confidence: 99%
“…3 Calcium antagonists that inhibit transmembrane calcium influx in cardiac and vascular smooth calcium antagonist synthesized by Takenaka and his colleagues, is a dihydropyridine derivative and a potent coronary and cerebral vasodilator (figure 1). [25][26][27][28][29][30][31][32][33] Nicardipine has been shown to relax the isolated canine coronary arterial strip twice as much as nifedipine, six times as much as nitroglycerin, 10 times as much as verapamil, and 80 times as much as diltiazem. 27 In anesthetized dogs nicardipine increases coronary blood flow to the same extent as nifedipine and three times as much as nitroglycerin, while it has much less effect on atrioventricular conduction and cardiac contractility when compared with verapamil and diltiazem.27…”
Section: In 1969 Maroko Et Al1'2 Demonstrated That Myocardi-mentioning
confidence: 99%